A search for top-squark pair production, in final states containing a top quark, a charm quark and missing transverse momentum, using the 139 fb-1 of pp collision data collected by the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; et al. (Journal of high energy physics, 2024)
This paper presents a search for top-squark pair production in final states with a top quark, a charm quark and missing transverse momentum. The data were collected with the ATLAS detector during LHC Run 2 and correspond to an integrated luminosity of 139 fb(-1) of proton-proton collisions at a centre-of-mass energy of root s = 13TeV. The analysis is motivated by an extended Minimal Supersymmetric Standard Model featuring a non-minimal flavour violation in the second- and third-generation squark sector. The top squark in this model has two possible decay modes, either (t) over tilde (1) -> c (chi) over tilde (0)(1) or (t) over tilde (1) -> t (chi) over tilde (0)(1), where the (chi) over tilde (0)(1) is undetected. The analysis is optimised assuming that both of the decay modes are equally probable, leading to the most likely final state of tc + E-T(miss). Good agreement is found between the Standard Model expectation and the data in the search regions. Exclusion limits at 95% CL are obtained in the m((t) over tilde1) vs . m((chi) over tilde (0)(1)) plane and, in addition, limits on the branching ratio of the (t) over tilde -> t (chi) over tilde (0)(1)1 decay as a function of m((t) over tilde (1)) are also produced. Top-squark masses of up to 800 GeV are excluded for scenarios with light neutralinos, and top-squark masses up to 600 GeV are excluded in scenarios where the neutralino and the top squark are almost mass degenerate.